Global Pandemic, Technology Booms and New Business Trends: The Case of Japan - Tan, Soo Kee (WILAYAH: The International Journal of East Asian Studies, 2021)
The outbreak of COVID-19 has reshaped business environments across the world. Minimal physical contact quickly becoming the standard practice for how everyone interacts, almost everything is going online and touchless. Japan, as one of the most technologically innovative nations in the world, its technology firms and IT industry have enjoyed a prosperous year. The new global business trend and market demand has created new growth opportunities for Japanese firms in reviving the slumping economy. By exploring new business trends and booms in technology sectors, the intent of this study is to examine the impact of COVID-19 on business. The first section includes a discussion on digitalization and global pandemic technology growth, including examples involving the United States and China. The second section is focused on Japan by examining the COVID-19 impact on Japan’s economy, business trends and how this situation has benefitted technology players in Japan. Using business performance records in terms of equity gain and revenue growth, the impact of COVID-19 on business across sectors is investigated, with emphasis on Japan’s digital business and industry of automation, robotics and sensor technology. It concludes that the impacts of COVID-19 on the ways of doing business will be long lasting, and is expected to continue benefitting digital business and technology sectors.